Convenient One‐Pot Synthesis of α‐Amino Phosphonates in Water Using p‐Toluenesulfonic Acid as Catalyst for the Kabachnik–Fields Reaction. Issue 2 (24th January 2013) - Wu, Mingshu; Liu, Rendie; Wan, Dehui
ABSTRACT The three‐component Kabachnik–Fields reaction of substituted salicylaldehydes, aromatic amine, and triphenyl phosphite in water was effectively catalyzed by p‐toluenesulfonic acid to give various α‐amino phosphonates in good yields. The catalyst is easily available and inexpensive, and the process is green and mild. © 2013 Wiley Periodicals, Inc. Heteroatom Chem 24:110–115, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/hc.21071